Efficacy of Performance Management on Organizational Commitment to Serve Police Personnel - Abdulhafis Adeyinka Hassan; Habibat Bolanle Abdulkareem; Ramota Funsho Sanni (Universitas Pendidikan Indonesia (UPI), 2023)
The importance of performance management cannot be underestimated in employee organizational commitment. Organizational commitment is a psychological link between an employee and his or her organization that makes it less likely that the employee will voluntarily leave the organization and the extent to which an employee develops an attachment and feels a sense of allegiance to his or her employer. Social exchange theory was used to anchor the study and the study considered employee welfare and job rotation among other performance management, descriptive statistic method was adopted and Pearson product-moment correlation was employed to analyze raised hypothesis, 150 serving police personnel was selected based on the purposive and convenient method. The result of the first hypothesis stated there is no significant relationship between employee welfare and employee organizational commitment was found significant (r= 0.711; p0.05). The second hypothesis stated there is no significant relationship between job rotation and employee organizational commitment was found significant (r= 0.179; p0.05). This study was recommended that Organizational leaders, instructors, and supervisors should develop positive connections that would result in increased employee level of wiliness to perform roles beyond their required role. Also, Police management should endeavor to necessary welfare to the employees in a manner that would enhance employees' desire to act or perform beyond their required role.